Cashew cultivation and research in Malaysia. - Abdul Ghani, I.; Abdul Razak, A. (1979)
Cashew, Anacardium occidentale is being grown extensively along the East Coast of West Malaysia. It is estimated that 3500 hectares are planted with Cashew plants. The area is covered with sandy bris soil where agriculture has not being able to establish itself. The growing of cashews provide raw materials for the setting up of processing plants, as well as opportunities for more employments. The cultivation of cashew have many problems. For example, the limiting factors affecting the yields are the poor fertility of the bris soil and the presence of mansoon an the East Coast. To make the matter worse, there is a shortage of harvesters at the peak of fruiting seasons. Many preliminary trials had been attempted by various agencies such as CIMA, MARDI and Department of Agriculture and Universities to solve some of the basic problems. In the past, there was a lack of inter-organisational research activities. The trend now is to have joint investigational work between various agencies with the hope of reducing duplication. The paper discusses the major problems of Cashew cultivation and some aspects of research in solving the problems.